Bond Buybacks and Exchanges : Background Note - World Bank Group (World Bank, Washington, DC, 2016)
This background note focuses on the use of bond buybacks and bond exchanges in the domestic government securities market. The objective is to provide an overview of their functions and of the procedures that facilitate their implementation, using country examples as illustrations.